Experimental study on direct tension behavior of concrete through combined digital image correlation and acoustic emission techniques. (23rd August 2019) - Guo, Yuzhu; Chen, Xudong; Yang, Hanqing; Hu, Liangpeng; Zhang, Jinhua; Fan, Xiangqian
Abstract: In order to investigate the fracture behavior of plain concrete under tensile load, uniaxial tensile test of plain concrete cylinder is carried out in this paper. Acoustic emission (AE) and 3D digital image correlation (3D DIC) are used to measure the internal acoustic emission signal and the surface deformation characteristics of the specimen. Before the tensile stress comes close to the peak, there is very little acoustic emission signal inside the specimen. When the tensile stress reaches the peak, the acoustic emission signal inside the specimen begins to increase dramatically, and the number of microcracks on the surface of the specimen increases and the crack width expands gradually. The experimental results are as follows: Acoustic emission can monitor the internal fracture damage of the specimen. The microcracks and macrocracks on the surface of the specimen can be monitored sensitively by 3D DIC. And the test results of the two methods are basically consistent and complementary. These results can provide some reference for the research of plain concrete under tensile load.